Genes of Different Catabolic Pathways Are Coordinately Regulated by Dal81 in Saccharomyces cerevisiae - Palavecino, Marcos D. (Hindawi Publishing Corporation, 2015)

(untitled) (J Amino Acids)
Yeast can use a wide variety of nitrogen compounds. However, the ability to synthesize enzymes and permeases for catabolism of poor nitrogen sources is limited in the presence of a rich one. This general mechanism of transcriptional control is called nitrogen catabolite repression. Poor nitrogen sources, such as leucine, γ-aminobutyric acid (GABA), and allantoin, enable growth after the synthesis of pathway-specific catabolic enzymes and permeases. This synthesis occurs only under conditions of nitrogen limitation and in the presence of a pathway-specific signal. In this work we studied the temporal order in the induction of AGP1, BAP2, UGA4, and DAL7, genes that are involved in the catabolism and use of leucine, GABA, and allantoin, three poor nitrogen sources. We found that when these amino acids are available, cells will express AGP1 and BAP2 in the first place, then DAL7, and at last UGA4. Dal81, a general positive regulator of genes involved in nitrogen utilization related to the metabolisms of GABA, leucine, and allantoin, plays a central role in this coordinated regulation.